Sketchbook of the Philadelphia & Boston Face Brick Co. - Philadelphia & Boston Face Brick Co. (Salt Lake City, UT : Project Gutenberg, 2022)
"Sketchbook of the Philadelphia & Boston Face Brick Co." is a historical publication authored by the Philadelphia & Boston Face Brick Company, produced in the early 20th century. This specialized volume showcases a series of ornamental brick designs meant for fireplace mantels, emphasizing both the aesthetic and practical benefits of using their products in home decoration. In the book, readers will find a detailed collection of sketches representing various fireplace mantel designs, each accompanied by dimensions and pricing for the specified bricks required for construction. The sketches reflect a wide range of styles, from simple and traditional to elegantly ornate, while highlighting the bricks in multiple colors such as red, cream, and gray. The text underscores the durability and artistic value of these mantels, suggesting they can beautifully enhance home interiors while being far superior to then-popular wooden alternatives. The focus on design compatibility with diverse interior themes makes the book a valuable resource for home builders and decorators interested in incorporating fine craftsmanship into their spaces. (This is an automatically generated summary.)
Release date is 2022-10-22
Tom Cosmas compiled from materials provided at The Internet Archive and placed in the Public Domain.
Keywords: Fireplaces; Architecture, Domestic; Bricks -- Catalogs